An emerging NIR super-long persistent phosphor and its applications. (June 2022) - Liu, S.; Cai, H.; Zhang, S.; Song, Z.; Liu, Q.
Abstract: Materials with the ability to persistently emit intense near-infrared (NIR) light after ceasing excitation are very useful in many fields. The persistent time is a vital parameter for successful applications. In this study, we developed an emerging NIR super-long persistent luminescent (PersL) material, Cr 3+ -activated magnetoplumbite oxide La(Zn/Mg)(Ga, Al)11 O19 :Cr 3+, by doping Yb 3+ as a new efficient electron trap and incorporating Al 3+ to engineer the energy band. We show that fine control of the trap depth and density is the key underpinning for PersL enhancement. The title material emits intense PersL in the spectral range of 600–950 nm with a PersL time of more than 1, 000 h. Furthermore, after undergoing such long-term decay, the NIR emission can be revived by photo-/thermo-stimulation. We demonstrate its potential uses in bioimaging, multilevel anti-counterfeiting, tracing, and positioning. This study provides insight into how energy band engineering manipulates electronic structures to achieve high-performance PersL. The new NIR persistent phosphor may be soon utilized in related applications. Graphical abstract: Image 1 Highlights: Super-long near-infrared persistent luminescence with 1, 000 h duration in La(Zn/Mg)(Ga, Al)11 O19 :Cr 3+, Yb 3+ is explored. Strategy of Yb 3+ co-dopant and energy band engineer is adopted to optimize the persistent performance. The potentials of in tissue-imaging, tracing, and multi-level anti-counterfeiting is demonstrated.